Hydrogen storage material and method for storing hydrogen

CN118125374BActive Publication Date: 2026-10-09SHANGHAI TIAN YANG STEEL TUBE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410252383.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-06
Publication Date
2026-10-09
Estimated Expiration
2044-03-06

AI Technical Summary

Technical Problem

然而由于镁基储氢材料缺乏有效的催化活性位点,导致其吸放氢动力学性能较差,且使用温度较高,因此亟需提供一种方案改善这一问题

Benefits of technology

[0005] The purpose of this invention is to provide a hydrogen storage material and a method for storing and releasing hydrogen thereon. By adding a main catalyst and a catalytic promoter, the catalytic active sites are improved, thereby promoting the hydrogen absorption and release performance of the magnesium-based hydrogen storage material and significantly reducing the hydrogen release temperature of the magnesium-based hydrogen storage material MgH2.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a hydrogen storage material and a hydrogen storage method thereof, and relates to the technical field of hydrogen storage materials.The hydrogen storage material provided by the application comprises the following components in percentage by weight: 3-5% of a main catalyst, 1-2% of a catalytic aid, and the rest of MgH2;the main catalyst comprises porous carbon and Pt and Pd active components adsorbed on the surface of the porous carbon, and the preparation method of the main catalyst comprises the following steps: putting porous carbon powder into an activation solution to stir and immerse, to obtain modified porous carbon powder; stirring and mixing the modified porous carbon powder with a mixed solution in which chloroplatinic acid and chloropalladic acid are dissolved, to obtain a mixed dispersion; stirring and dissolving a reducing agent and a stabilizer into the mixed dispersion, and then standing and precipitating; separating and washing the precipitate, and then drying, to obtain the main catalyst.The hydrogen storage material provided by the application can promote the hydrogen absorption and release performance of a magnesium-based hydrogen storage material, and greatly reduces the hydrogen release temperature of the magnesium-based hydrogen storage material MgH2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of hydrogen storage materials, and in particular to a hydrogen storage material and a method for storing and releasing hydrogen. Background Technology

[0002] Hydrogen energy has attracted much attention as a new energy source of the 21st century due to its high efficiency, cleanliness, and renewability. However, the development and utilization of hydrogen energy involves four key technologies: hydrogen preparation, storage, transportation, and application. Because hydrogen is flammable and explosive, and has low volumetric energy density at room temperature and pressure, hydrogen storage technology has become a bottleneck for the practical application and large-scale development of hydrogen energy.

[0003] Currently, the main hydrogen storage technologies are high-pressure gaseous hydrogen storage and cryogenic liquefaction hydrogen storage. However, both of these methods have obvious technical drawbacks. For example, although high-pressure gaseous hydrogen storage is simple and commonly used, it has low volumetric energy and high requirements for high-pressure containers. There are also certain dangers in the high-pressure hydrogen addition process. On the other hand, although cryogenic liquefaction hydrogen storage has a high energy density, it requires a lot of energy to liquefy hydrogen and has strict requirements for the low-temperature performance of storage equipment.

[0004] Compared to high-pressure gaseous hydrogen storage and cryogenic liquid hydrogen storage, solid-state hydrogen storage offers advantages such as high hydrogen storage density, good safety, and low cost, making it the most promising hydrogen energy storage and transportation method for the future. Among various solid-state hydrogen storage materials, magnesium-based solid-state hydrogen storage materials (MgH2) possess advantages such as high mass hydrogen storage density, reversible hydrogen absorption and desorption processes, abundant resources, low price, and environmental friendliness. However, due to the lack of effective catalytic active sites, magnesium-based hydrogen storage materials exhibit poor hydrogen absorption and desorption kinetics and require high operating temperatures. Therefore, there is an urgent need to provide a solution to address this issue. Summary of the Invention

[0005] The purpose of this invention is to provide a hydrogen storage material and a method for storing and releasing hydrogen thereon. By adding a main catalyst and a catalytic promoter, the catalytic active sites are improved, thereby promoting the hydrogen absorption and release performance of the magnesium-based hydrogen storage material and significantly reducing the hydrogen release temperature of the magnesium-based hydrogen storage material MgH2.

[0006] In a first aspect, the present invention provides a hydrogen storage material comprising, by weight percentage: 3-5% main catalyst, 1-2% catalyst promoter and balance MgH2; the main catalyst comprises porous carbon and Pt and Pd active components adsorbed on the surface of the porous carbon, and the preparation method of the main catalyst comprises the following steps: immersing porous carbon powder in an activation solution by stirring to obtain modified porous carbon powder; mixing the modified porous carbon powder with a mixed solution containing chloroplatinic acid and chloropalladic acid by stirring to obtain a mixed dispersion; adding a reducing agent and a stabilizer to the mixed dispersion by stirring to dissolve, allowing it to stand and precipitate; separating and washing the precipitate and drying it to obtain the main catalyst.

[0007] Optionally, when the porous carbon powder is immersed in the activation solution and stirred, the solute in the activation solution includes a silane coupling agent, and the silane coupling agent includes at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and the mass ratio of the porous carbon powder to the silane coupling agent dissolved in the activation solution is 1:(3-5).

[0008] Optionally, after mixing the modified porous carbon powder with a mixed solution containing chloroplatinic acid and chloropalladium acid to obtain a mixed dispersion, the mass ratio of the modified porous carbon powder, chloroplatinic acid, and chloropalladium acid in the mixed dispersion is 1:(0.1-0.2):(0.1-0.2).

[0009] Optionally, during the process of adding a reducing agent and a stabilizer to the mixed dispersion and stirring to dissolve them, the stabilizer includes at least one of polyvinylpyrrolidone, polyethylene glycol, and acetylacetone, and the reducing agent includes at least one of sodium borohydride, ascorbic acid, and glucose.

[0010] Optionally, after adding a reducing agent and a stabilizer to the mixed dispersion and stirring to dissolve them, the concentration of the reducing agent is 3-8 g / mL and the concentration of the stabilizer is 1-3 g / mL.

[0011] Optionally, the method for preparing the porous carbon powder includes the following steps: carbonizing a biomass carbon source by high-temperature heat treatment under a non-oxidizing gas and then grinding it to obtain a primary carbon material; and then performing vapor phase deposition on the primary carbon material under a carbon source gas to obtain porous carbon powder; wherein the biomass carbon source includes at least one of straw, bamboo, citrus peel, grapefruit peel, and rice husk, and the carbon source gas includes at least one of methane, ethane, propane, acetylene, and ethylene.

[0012] Optionally, the catalyst is ruthenium oxide.

[0013] Secondly, the present invention provides a method for preparing a hydrogen storage material, comprising the following steps: under an inert atmosphere and / or a nitrogen atmosphere, a main catalyst, a catalyst promoter and MgH2 are ball-milled intermittently in both forward and reverse directions for 4-5 hours at a ball-to-material ratio of 200-300 and a ball milling speed of 100-200 rpm to obtain a hydrogen storage material.

[0014] Thirdly, the present invention provides a method for storing hydrogen using a hydrogen storage material, comprising the following steps: placing the hydrogen storage material after releasing hydrogen in an environment with a hydrogen pressure of 2-3 MPa and a temperature of 300-350°C for hydrogen storage.

[0015] Fourthly, the present invention provides a method for releasing hydrogen from a hydrogen storage material, comprising the following steps: heating the hydrogen storage material to 110-120°C until it begins to release hydrogen, and releasing 6.8-6.9 wt% hydrogen gas when the hydrogen storage material is heated to 170-180°C. Detailed Implementation

[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art to which this invention pertains.

[0017] This invention provides a hydrogen storage material comprising, by weight percentage: 3-5% main catalyst, 1-2% catalyst promoter, and the balance MgH2; the main catalyst comprises porous carbon and Pt and Pd active components adsorbed on the surface of the porous carbon. In practice, the catalyst promoter is ruthenium oxide. When ruthenium oxide and the main catalyst are mixed together with MgH2, the catalytic effect of the main catalyst can be significantly enhanced, thereby substantially reducing the hydrogen desorption temperature.

[0018] Specifically, the preparation method of the main catalyst includes the following steps:

[0019] S1. Modified porous carbon powder is obtained by immersing porous carbon powder in an activation solution and stirring.

[0020] S2. The modified porous carbon powder is stirred and mixed with a mixed solution containing chloroplatinic acid and chloropalladium acid to obtain a mixed dispersion.

[0021] S3. Add reducing agent and stabilizer to the mixed dispersion, stir to dissolve, let stand to precipitate, separate and wash the precipitate, and then dry to obtain the main catalyst.

[0022] In some embodiments, step S0 is performed before step S1, in which the biomass carbon source is carbonized by high-temperature heat treatment under a non-oxidizing gas and then ground to obtain a primary carbon material. The primary carbon material is then vapor-deposited under a carbon source gas to obtain porous carbon powder.

[0023] Specifically, when performing step S0, the biomass carbon source used includes at least one of straw, bamboo, citrus peel, grapefruit peel, and rice husk, and the carbon source gas used includes at least one of methane, ethane, propane, acetylene, and ethylene.

[0024] Specifically, when performing step S0, the primary carbon material is vapor-deposited under a carbon source gas, the vapor-deposit temperature is controlled at 700-800℃, and the pressure of the carbon source gas is controlled at 0.3-0.5MPa.

[0025] In some embodiments, when performing step S1, in which the porous carbon powder is immersed in the activation solution by stirring, the solute in the activation solution includes a silane coupling agent, and the silane coupling agent used includes at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-β(aminoethyl)-γ-aminopropyltrimethoxysilane. Specifically, the solvent portion of the activation solution may be an alcohol-water mixture.

[0026] In some embodiments, when the porous carbon powder is immersed in the activation solution in step S1, the particle size DV50 of the porous carbon powder is 5-8 μm, and after the porous carbon powder is immersed in the activation solution, it can be uniformly dispersed by ultrasonic dispersion.

[0027] In some embodiments, when performing step S1, the porous carbon powder is immersed in the activation solution and stirred, the mass ratio of the porous carbon powder to the silane coupling agent dissolved in the activation solution is 1:(3-5).

[0028] In some embodiments, after performing step S2, the modified porous carbon powder is stirred and mixed with a mixed solution containing chloroplatinic acid and chloropalladium acid to obtain a mixed dispersion, the mass ratio of the modified porous carbon powder, the chloroplatinic acid, and the chloropalladium acid in the mixed dispersion is 1:(0.1-0.2):(0.1-0.2).

[0029] In some embodiments, during the process of adding the reducing agent and stabilizer to the mixed dispersion in step S3 and stirring to dissolve them, the stabilizer includes at least one of polyvinylpyrrolidone, polyethylene glycol, and acetylacetone, and the reducing agent includes at least one of sodium borohydride, ascorbic acid, and glucose.

[0030] Specifically, after adding a reducing agent and a stabilizer to the mixed dispersion and stirring to dissolve them, the concentration of the reducing agent is 3-8 g / mL and the concentration of the stabilizer is 1-3 g / mL.

[0031] The present invention also provides a method for preparing hydrogen storage material in any of the above embodiments, comprising the following steps: under an inert atmosphere and / or a nitrogen atmosphere, the main catalyst, the catalyst promoter and MgH2 are ball-milled intermittently in both forward and reverse directions for 4-5 hours at a ball-to-material ratio of 200-300 and a ball milling speed of 100-200 rpm to obtain the hydrogen storage material.

[0032] The present invention also provides a method for storing hydrogen using the hydrogen storage material in any of the above embodiments, comprising the following steps: placing the hydrogen storage material after releasing hydrogen in an environment with a hydrogen pressure of 2-3 MPa and a temperature of 300-350°C for hydrogen storage.

[0033] The present invention also provides a method for releasing hydrogen from the hydrogen storage material in any of the above embodiments, comprising the following steps: heating the hydrogen storage material to 110-120°C until it begins to release hydrogen, and releasing 6.8-6.9 wt% hydrogen gas when the hydrogen storage material is heated to 170-180°C.

[0034] Example 1

[0035] This embodiment 1 provides a method for preparing a hydrogen storage material, including the following steps:

[0036] S0. After grinding the straw through a 100-mesh sieve, the temperature was raised to 900℃ and held for 5 hours under an argon atmosphere. After carbonization treatment, the primary carbon material was ground to obtain a primary carbon material. The primary carbon material was vapor-deposited at 800℃, a methane gas flow rate of 1 slm, and a pressure of 0.5 MPa for 30 minutes and then cooled to room temperature in the furnace. The obtained product was then pulverized by airflow to make its particle size DV50 5-8 μm, and then porous carbon powder was obtained.

[0037] S1. Porous carbon powder is added to an activation solution containing γ-aminopropyltriethoxysilane (the solvent is a mixture of ethanol and water in a volume ratio of 1:1), and ultrasonically dispersed for 1 hour at an ultrasonic power of 200W. After filtration and drying, modified porous carbon powder is obtained. The mass ratio of porous carbon powder to γ-aminopropyltriethoxysilane is 1:3.

[0038] S2. The modified porous carbon powder is stirred and mixed with a mixed solution containing chloroplatinic acid and chloropalladium acid to obtain a mixed dispersion, wherein the mass ratio of modified porous carbon powder, chloroplatinic acid and chloropalladium acid in the mixed dispersion is 1:(0.1-0.2):(0.1-0.2);

[0039] S3. Add sodium borohydride at a concentration of 3-8 g / mL and polyvinylpyrrolidone at a concentration of 1-3 g / mL to the mixed dispersion, stir to dissolve, let stand to precipitate, separate and wash the precipitate, and then dry to obtain the main catalyst.

[0040] S4. After mixing 4wt% of the main catalyst, 2wt% of ruthenium oxide and the balance MgH2, the mixture is ball-milled intermittently in both forward and reverse directions for 5 hours under an argon atmosphere, a ball-to-material ratio of 200-300 and a ball milling speed of 100-200 rpm to obtain the hydrogen storage material.

[0041] Comparative Example 1

[0042] Comparative Example 1 provides a method for preparing a hydrogen storage material, including the following steps:

[0043] S0. After grinding the straw through a 100-mesh sieve, the temperature was raised to 900℃ and held for 5 hours under an argon atmosphere. After carbonization treatment, the primary carbon material was ground to obtain a primary carbon material. The primary carbon material was vapor-deposited at 800℃, a methane gas flow rate of 1 slm, and a pressure of 0.5 MPa for 30 minutes and then cooled to room temperature in the furnace. The obtained product was then pulverized by airflow to make its particle size DV50 5-8 μm, and then porous carbon powder was obtained.

[0044] S1. Porous carbon powder is added to an activation solution containing γ-aminopropyltriethoxysilane (the solvent is a mixture of ethanol and water in a volume ratio of 1:1), and ultrasonically dispersed for 1 hour at an ultrasonic power of 200W. After filtration and drying, modified porous carbon powder is obtained. The mass ratio of porous carbon powder to γ-aminopropyltriethoxysilane is 1:3.

[0045] S2. The modified porous carbon powder is stirred and mixed with a mixed solution containing chloroplatinic acid and chloropalladium acid to obtain a mixed dispersion, wherein the mass ratio of modified porous carbon powder, chloroplatinic acid and chloropalladium acid in the mixed dispersion is 1:(0.1-0.2):(0.1-0.2);

[0046] S3. Add sodium borohydride at a concentration of 3-8 g / mL and polyvinylpyrrolidone at a concentration of 1-3 g / mL to the mixed dispersion, stir to dissolve, let stand to precipitate, separate and wash the precipitate, and then dry to obtain the main catalyst.

[0047] S4. After mixing 6wt% of the main catalyst with the balance MgH2, the mixture is ball-milled intermittently in both forward and reverse directions for 5 hours under an argon atmosphere, a ball-to-material ratio of 200-300, and a ball milling speed of 100-200 rpm to obtain the hydrogen storage material.

[0048] Comparative Example 2

[0049] Comparative Example 2 provides a method for preparing a hydrogen storage material, including the following steps:

[0050] S1. After mixing 6wt% ruthenium oxide with the balance MgH2, the mixture is ball-milled intermittently in both forward and reverse directions for 5 hours under an argon atmosphere, a ball-to-material ratio of 200-300, and a ball milling speed of 100-200 rpm to obtain a hydrogen storage material.

[0051] Performance testing

[0052] The hydrogen desorption kinetics of the hydrogen storage materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 were tested using a HyEnergy PCTPro 2000 gas desorption instrument. The hydrogen storage materials after saturated adsorption were placed in an argon atmosphere, and a desorption test was conducted with a starting temperature of 20°C. The initial hydrogen desorption temperature and peak hydrogen desorption temperature of the three hydrogen storage materials were tested, and the results are shown in Table 1 below. The hydrogen desorption performance of the saturated adsorption hydrogen storage materials was tested at the peak hydrogen desorption temperature, and the total amount of hydrogen desorption was recorded, and the results are shown in Table 1 below.

[0053] Table 1 Hydrogen release performance test

[0054] Example 1 112.4 176.5 6.9 Comparative Example 1 143.8 224.1 6.8 Comparative Example 2 273.6 417.6 6.8

[0055] As can be seen from Table 1, the hydrogen storage material provided by the present invention has a low peak hydrogen release temperature, which indicates that the hydrogen storage material provided by the present invention can be well applied to hydrogen storage and transportation. Furthermore, as can be seen from Comparative Example 2, the use of ruthenium oxide alone has no significant promoting effect on the hydrogen release of MgH2, while the combination of the main catalyst and ruthenium oxide in Example 1 can significantly improve the catalytic effect of the main catalyst and significantly reduce the temperature required for MgH2 to release hydrogen.

[0056] While embodiments of the present invention have been described in detail above, it will be apparent to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations fall within the scope and spirit of the invention as set forth in the claims. Furthermore, the invention described herein may have other embodiments and can be implemented or carried out in various ways.

Claims

1. A hydrogen storage material, characterized in that, The catalyst comprises, by weight percentage: 3-5% main catalyst, 1-2% catalyst promoter, and the balance MgH2; the main catalyst comprises porous carbon and Pt and Pd active components adsorbed on the surface of the porous carbon, and the preparation method of the main catalyst includes the following steps: porous carbon powder is immersed in an activation solution and stirred to obtain modified porous carbon powder; the modified porous carbon powder is mixed with a mixed solution containing chloroplatinic acid and chloropalladium acid to obtain a mixed dispersion; a reducing agent and a stabilizer are added to the mixed dispersion, stirred to dissolve, allowed to stand and precipitate, the precipitate is separated, washed, and dried to obtain the main catalyst; the catalyst promoter is ruthenium oxide. The method for preparing the porous carbon powder includes the following steps: carbonizing a biomass carbon source by high-temperature heat treatment under a non-oxidizing gas and then grinding it to obtain a primary carbon material; depositing the primary carbon material in a carbon source gas to obtain porous carbon powder; when the porous carbon powder is immersed in an activation solution and stirred, the solute in the activation solution includes a silane coupling agent, and the silane coupling agent includes at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, and the mass ratio of the porous carbon powder to the silane coupling agent dissolved in the activation solution is 1:(3-5).

2. The hydrogen storage material according to claim 1, characterized in that, After mixing the modified porous carbon powder with a mixed solution containing chloroplatinic acid and chloropalladium acid to obtain a mixed dispersion, the mass ratio of the modified porous carbon powder, chloroplatinic acid, and chloropalladium acid in the mixed dispersion is 1:(0.1-0.2):(0.1-0.2).

3. The hydrogen storage material according to claim 1, characterized in that, During the process of adding reducing agent and stabilizer to the mixed dispersion and stirring to dissolve them, the stabilizer includes at least one of polyvinylpyrrolidone, polyethylene glycol, and acetylacetone, and the reducing agent includes at least one of sodium borohydride, ascorbic acid, and glucose.

4. The hydrogen storage material according to claim 3, characterized in that, After adding reducing agent and stabilizer to the mixed dispersion and stirring to dissolve, the concentration of the reducing agent is 3-8 g / mL and the concentration of the stabilizer is 1-3 g / mL.

5. The hydrogen storage material according to claim 1, characterized in that, The biomass carbon source includes at least one of straw, bamboo, citrus peel, grapefruit peel, and rice husk, and the carbon source gas includes at least one of methane, ethane, propane, acetylene, and ethylene.

6. A method for preparing a hydrogen storage material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Hydrogen storage material is prepared by intermittent ball milling of the main catalyst, catalyst promoter and MgH2 in an inert atmosphere and / or a nitrogen atmosphere, at a ball-to-material ratio of 200-300 and a ball milling speed of 100-200 rpm, in both forward and reverse directions for 4-5 hours.

7. A method for storing hydrogen using a hydrogen storage material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: After releasing hydrogen, the hydrogen storage material is placed in an environment with a hydrogen pressure of 2-3 MPa and a temperature of 300-350℃ for hydrogen storage.

8. A method for releasing hydrogen from a hydrogen storage material as described in any one of claims 1 to 5, characterized in that, The process includes the following steps: heating the hydrogen storage material to 110-120°C until it begins to release hydrogen, and releasing 6.8-6.9 wt% of hydrogen gas when the hydrogen storage material is heated to 170-180°C.

Citation Information

Patent Citations

  • Heterogeneous hydrogen-catalyst reactor

    CN102164849A

  • Hydrogen storage composites and methods for manufacturing the same

    CN103183313A

  • Preparation method of fuel cell anode catalyst

    CN104549233A

  • Catalyst for hydrodechlorination and preparation method thereof

    CN114797846A

  • Porous carbon, silicon-carbon negative electrode material and preparation method of porous carbon

    CN115676825A